Living Alone or With Others and Depressive Symptoms, and Effect Modification by Residential Social Cohesion Among Older Adults in Japan: The JAGES Longitudinal Study - Honjo, Kaori (J Epidemiol, 2018)
BACKGROUND: There is little longitudinal evidence on the impact of specific living arrangements (ie, who individuals live with) on mental health among older adults, and no studies have examined the modifying effect of residential social cohesion level on this association. We aimed to examine the association between living arrangements and depressive symptoms and whether this association varies with residential neighborhood social cohesion level among 19,656 men and 22,513 women aged 65 years and older in Japan. METHODS: We analyzed the association between baseline living arrangements in 2010 and depressive symptoms in 2013. We calculated gender-specific odds ratios (ORs) of living arrangements for depressive symptoms using a logistic regression and conducted subgroup analyses by neighborhood social cohesion level. RESULTS: Among men (but not women), living alone (OR 1.43; 95% confidence intervals [CI], 1.18–1.73) and living with spouse and parent (OR 1.47, 95% CI, 1.09–1.98) were associated with increased odds of depressive symptoms compared with living with a spouse only. Living with spouse and child was a risk for men in the young age group but a protective factor for women. We also identified that the negative impact of living arrangements on depressive symptoms was attenuated in neighborhoods with higher levels of social cohesion. CONCLUSIONS: Living arrangements are associated with risk of depressive symptoms among men and women; these associations differ by gender and neighborhood social cohesion level. Our results suggest the need to pay more attention to whether individuals live alone, as well as who individuals live with, to prevent depressive symptoms among older adults.